2022
DOI: 10.3390/microorganisms10071366
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Nucleotide Variants Associated with Resistance to Nine Antimicrobials in Mycoplasma bovis

Abstract: Antimicrobial resistance (AMR) studies of Mycoplasma bovis have generally focused on specific loci versus using a genome-wide association study (GWAS) approach. A GWAS approach, using two different models, was applied to 194 Mycoplasma bovis genomes. Both a fixed effects linear model (FEM) and a linear mixed model (LMM) identified associations between nucleotide variants (NVs) and antimicrobial susceptibility testing (AST) phenotypes. The AMR phenotypes represented fluoroquinolones, tetracyclines, phenicols, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
(144 reference statements)
1
5
0
Order By: Relevance
“…These results can indicate the possibility of our findings regarding similar resistance genes to be integrated into chromosomes of the metagenome, explaining their absence in the plasmidomes. This hypothesis is supported by other genomic studies where the ARGs related to fluoroquinolone and tetracycline resistance are associated with the bacterial chromosome [33], [34].…”
Section: B Resistome Annotation Of Whole Metagenome and Plasmidomes P...supporting
confidence: 73%
“…These results can indicate the possibility of our findings regarding similar resistance genes to be integrated into chromosomes of the metagenome, explaining their absence in the plasmidomes. This hypothesis is supported by other genomic studies where the ARGs related to fluoroquinolone and tetracycline resistance are associated with the bacterial chromosome [33], [34].…”
Section: B Resistome Annotation Of Whole Metagenome and Plasmidomes P...supporting
confidence: 73%
“…L1 serves as a ribosomal protein to bind rRNA and as a translational repressor binding its mRNA [63]. Studies in Mycoplasma bovis and Stenotrophomonas maltophilia have found that mutations in both L1 and L4 proteins were independently associated with elevated macrolide MICs [64,65]. For example, a genome wide association study in Mycoplasma bovis identified nucleotide variants in L1 and L4 as independently associated with macrolide MICs [65].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the genes of ABC efflux pumps in the mechanism of antibacterial resistance in mycoplasmas has been previously described ( Pereyre et al, 2002 ; Raherison et al, 2002 , 2005 ; Antunes et al, 2015 ; Chernova et al, 2016 ), in contrast to other families of transport proteins. Furthermore, nsSNPs have been reported in the ABC efflux gene encoding regions of M. bovis ( Waldner et al, 2022 ), M. pneumoniae ( Li et al, 2017 ), and Streptococcus pneumoniae ( Lupien et al, 2013 ), as well as in the RND pumps of other bacterial species such as Acinetobacter baumannii, Escherichia coli, Legionella pneumophila, Neisseria gonorrhoeae, Pseudomonas aeruginosa , and Salmonella enterica ( Zwama and Nishino, 2021 ). SNPs related to antibiotic resistance have also been described in the promoter regions of efflux pumps, specifically in N. gonorrhoeae and Staphylococcus aureus ( Kaatz et al, 1999 ; Unemo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been published that have identified mutations associated with antibiotic resistance in the coding regions ( Lupien et al, 2013 ; Zwama and Nishino, 2021 ; Waldner et al, 2022 ) or the promoters ( Kaatz et al, 1999 ; Unemo et al, 2019 ) of various efflux pump genes in other bacteria. In the mechanism of antibacterial resistance of mycoplasmas, despite the presence of other transport protein families, only the significance of ABC efflux pumps has been previously established ( Pereyre et al, 2002 ; Raherison et al, 2005 ; Antunes et al, 2015 ; Chernova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation